Up-regulation by overexpression of c-MET in fibroblastic foci of usual interstitial pneumonia - Melocchi, Laura; Cervi, Giulia; Sartori, Giuliana; Gandolfi, Laura; Jocollé, Genny; Cavazza, Alberto; Rossi, Giulio (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2023)
Background. Usual interstitial pneumonia (UIP) is the radiologic and histologic hallmark of idiopathic pulmonary fibrosis (IPF) and the commonest histologic pattern of other progressive fibrosing interstitial lung diseases (e.g., fibrotic hypersensitivity pneumonia). Analogous to lung cancer, activation of epithelial-to-mesenchymal transition (EMT) is one of the main molecular pathways recently identified by transcriptomic studies in IPF. Fibroblastic foci (FF) are considered the active/trigger component of UIP pattern. The proto-oncogene C-MET is a key gene among molecules promoting EMT against which several inhibitors are currently available or promising in ongoing studies on lung cancer. Methods. Twenty surgical cases of diffuse fibrosing interstitial lung diseases (fILD) with UIP pattern and FF-rich (17 IPF and 3 patients with fibrotic hypersensitivity pneumonia, fHP) were retrospectively selected. FF were manually microdissected and analysed for c-MET gene alterations (FISH amplification and gene hot-spot mutations Sanger sequencing) and tested with a c-MET companion diagnostic antibody (clone SP44 metmab) by immunohistochemistry. Results. FF are characterized by upregulation of c-MET as shown by overexpression of the protein in 80% of cases, while no gene amplification by FISH or mutations were detected. C-MET upregulation of FF was observed either in IPF and fHP, with a tropism for the epithelial cell component only. Conclusion. Upregulation of c-MET in FF of ILD with UIP pattern further confirms the key role of the proto-oncogene c-MET in its pathogenesis, possibly representing an interesting and easily-detectable molecular target for selective therapy using specific inhibitors in future clinical trials, similar to lung cancer. It is reasonable to speculate that molecular alterations in FF can also be detected in FF by transbronchial cryobiopsy. Key words: UIP, IPF, fibroblast foci, c-MET, immunohistochemistry, PCR.read more